2013
DOI: 10.1093/mnras/stt1766
|View full text |Cite
|
Sign up to set email alerts
|

The structure and fate of white dwarf merger remnants

Abstract: We present a large parameter study where we investigate the structure of white dwarf (WD) merger remnants after the dynamical phase. A wide range of WD masses and compositions are explored and we also probe the effect of different initial conditions. We investigated the degree of mixing between the WDs, the conditions for detonations as well as the amount of gas ejected. We find that systems with lower mass ratios have more total angular momentum and as a result more mass is flung out in a tidal tail. Nuclear … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
271
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(285 citation statements)
references
References 105 publications
13
271
1
Order By: Relevance
“…combinations. This tendency of weak dependence on the resolution has already been reported in previous studies (Raskin et al 2012;Dan et al 2014). …”
Section: Numerical Resolutionsupporting
confidence: 86%
See 2 more Smart Citations
“…combinations. This tendency of weak dependence on the resolution has already been reported in previous studies (Raskin et al 2012;Dan et al 2014). …”
Section: Numerical Resolutionsupporting
confidence: 86%
“…Zhu et al (2013) mainly focused on the (early) remnant phase and the resolutions of their simulations are lower than those in our study. Although Dan et al (2012Dan et al ( , 2014 covered the merger phase and remnant phase, their numerical resolution is much lower than ours. We expect that SN Ia explosions occur not only in the early remnant phase but also in the dynamic merger phase.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In particular, Nomoto & Kondo (1991) show that the merger product evolves towards an accretion-induced collapse (AIC) rather than towards a normal SN Ia. Only recently, some studies indicate that the merger can lead to a SN Ia explosion under certain circumstances (Pakmor et al 2010(Pakmor et al , 2011(Pakmor et al , 2013Shen et al 2013;Dan et al 2014). Finally, binary population synthesis (BPS) studies show that neither channel reproduces the observed SN Ia rate (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the detonation occurred self-consistently and did not need to be intentionally triggered using an external source term. Dan et al (2012Dan et al ( , 2014 performed a large sweep of the parameter space for merger pairs and found that pure carbon-oxygen systems would generally not lead to detonations (and thus be violent mergers) except for the most massive systems. They did find that for systems with WDs containing helium, many would detonate and potentially lead to SNe Ia, either through the aforementioned instabilities in the accretion stream, or during the contact phase, similar to the violent carbon-oxygen WD mergers.…”
Section: Introductionmentioning
confidence: 99%